Neglected lesser tuberosity avulsion in an adolescent elite gymnast. Issue 3 (July 2014) - Paxinos, Odysseas; Karavasili, Alexandra; Manolarakis, Manolis; Paxinos, Thrasivoulos; Papavasiliou, Athanasios
We report the case of a 16-year-old elite gymnast who presented with recurring pain in the left shoulder after training. The athlete recalled an injury to the shoulder 2 years ago. Clinically a localized tenderness to the anterior shoulder and loss of strength and range of motion was noted. Imaging investigation suggested a neglected lesser tuberosity avulsion. The athlete was treated with open excision of the deformed tuberosity and direct repair of the subscapularis to the humeral head. Following a careful postoperative rehabilitation protocol the athlete was able to return to unrestricted gymnastics after 6 months. After surgery the athlete followed a intense rehabilitation program that allowed him to return to sports at 6 months. At 5-years follow-up, the athlete was asymptomatic and competing at an international level. Avulsion fractures of the lesser tuberosity are extremely rare injuries with significant shoulder disability if left untreated. Anatomic repair can yield excellent results, even in neglected cases.